HARMONISASI PERDA NOMOR 4 TAHUN 2011 TENTANG RTRW KOTA MALANG DENGAN PERUNDANG-UNDANGAN BIDANG LINGKUNGAN HIDUP - Surya Anoraga (Faculty of Law, University of Muhammadiyah Malang, 2017)
Law that positively regulates the imposition of civil sanctionx, administrative sanctions and criminal sanctions as regulated in Law Number 26 of 2007 on Spatial Planning and more on the local regulation Malang No. 4 of 2011 on Spatial Planning Malang Year 2010- 2030 (RTRW). Administrative and criminal sanctions as a sanction premium remedium while criminal sanctions as a sanction ultimum remedium. Former Act and regulation are still not meticulous in designing/forming. That is evidenced still weakness in some of the provisions in the legislation are still related to civil sanctions, administrative and ceiminal. The legislator has not been meticulous in making decisions RTRW. Hence it need for harmonization between laws and regulations both at the level of local regulations and at the level of the Act.